Potential for a cerebellar role in moderate-late preterm associated behavioural disorders - Pavy, Carlton L.; Shaw, Julia C.; Moloney, Roisin A.; Palliser, Hannah K.; Hirst, Jonathon J. (Frontiers in Pediatrics, 2024)
Preterm birth is known to cause impaired cerebellar development, and this is associated with the 13 development of neurobehavioral disorders. This review aims to identify the mechanisms through which 14 preterm birth impairs cerebellar development and consequently, increases the risk of developing 15 neurobehavioral disorders. The severity of these disorders is directly related to the degree of 16 prematurity, but it is also evident that even late preterm births are at significantly increased risk of 17 developing serious neurobehavioral disorders. Preterm birth is associated with hypoxic events and 18 increased glutamatergic tone within the neonatal brain which contribute to excitotoxic damage. The 19 cerebellum is a dense glutamatergic region which undergoes relatively late neurodevelopment up to 20 and beyond birth. Evidence indicates that the cerebellum forms reciprocal connections to regions 21 important in behaviour regulation such as the limbic system and frontal cortex. Studies using fMRI 22 (functional magnetic resonance Imaging), BOLD (blood oxygen level dependent) response and 23 morphology studies in humans show the cerebellum is often involved in disorders such as attention 24 deficit hyperactivity disorder (ADHD) and anxiety. The vulnerability of the cerebellum to preterm birth 25 insult and its connections to behaviour associated brain regions implicates it in the development of 26 neurobehavioral disorders. Protection against preterm associated insults on the cerebellum may provide 27 a novel avenue through which ADHD and anxiety can be reduced in children born preterm.